Transistor clamped five level inverter using non-inverting double reference single carrier PWM technique for photovoltaic applications - Bhaskar, M.S.; Padmanaban, Sanjeevikumar; Fedak, V.; Blaabjerg, Frede; Wheeler, Patrick (Rheinisch-Westfaelische Technische Hochschule Aachen, 2016)
This treatise deals with transistor clamped five level inverter Using Non-Inverting Double Reference Single Carrier PWM (NIDRSC PWM) Technique. Conventional or two level inverter have drawbacks like i) Requirement of fast switching devices ii) Very high dv/dt iii) High Electromagnetic Interferences (EMI) iv) Bulky filters v) Faster heating of switches and vi) Not suitable for high voltage applications. Multilevel Inverters (MLIs) are engaged to conquer the drawbacks of conventional two levels inverter. MLIs generate an AC voltage using small voltage steps obtained with the help of DC supplies or capacitor banks. To design the proposed five level inverter 5 numbers of power control switches and 8 diodes are required. The proposed inverter circuitry is investigated by using Non-Inverting Double Reference Single Carrier PWM (NIDRSC PWM) Technique in terms of harmonics content in output waveform. Under-modulation (modulation Index =0.85), unity (modulation Index =1) and over-modulation (modulation Index =1.25) PWM signal is obtained to drive control switches. Simulation results will confirm the functionality, design and operation of the proposed MLI and NIDRSC PWM Technique